Ceftobiprole for the treatment of pneumonia: a European perspective - Liapikou A; Cillóniz C; Torres A (Dove Medical Press, 2015)
Adamantia Liapikou,1 Catia Cillóniz,2 Antonio Torres216th Respiratory Department, Sotiria Chest Diseases Hospital, Athens, Greece; 2Pulmonology Department, Clinic Institute of Thorax (ICT), Hospital Clinic of Barcelona, Spain Insitut d’Investigacions Biomèdiques August Pi i Sunyer (IDIBAPS), Barcelona, SpainAbstract: Ceftobiprole, a new broad spectrum, parenteral cephalosporin, exhibits potent in vitro activity against a number of Gram-positive pathogens, including methicillin-resistant Staphylococcus aureus and penicillin-resistant Streptococcus pneumoniae, and Gram-negative pathogens associated with hospital-acquired pneumonia (HAP) and community-acquired pneumonia (CAP). Ceftobiprole has demonstrated noninferiority in two large-scale pivotal studies comparing it to ceftriaxone with or without linezolid in CAP, with clinical cure rates 86.6% versus 87.4%, or ceftazidime in HAP, with clinical cure rates of 77% versus 76%, respectively. However, ceftobiprole was inferior in the subgroup of patients undergoing mechanical ventilation. Ceftobiprole has so far demonstrated a good safety profile in preliminary studies, with similar tolerability to comparators. The most commonly observed adverse events of ceftobiprole included headache and gastrointestinal upset. It is the first cephalosporin monotherapy approved in the EU for the treatment of both CAP and HAP (excluding ventilator-associated pneumonia).Keywords: antibiotic resistance, methicillin-resistant staphylococci, community-acquired pneumonia, hospital-acquired pneumonia, cephalosporins